The characteristics of selected triaxiality measures of the stresses for a C(T) specimen dominated by the plane strain state - Graba, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a comprehensive analysis of the stress field and selected triaxiality parameters near the crack tip for C(T) specimen dominated by the plane strain state using the finite element method. It includes some theoretical information about elastic-plastic fracture mechanics, the basics of the FEM modeling and presentation of the numerical results.
Keywords: fracture mechanics; C(T); FEM; stress triaxiality parameter; Lode parameters; constraints; plane strain